Bondgraphs model on cavitating pump system. (2015) - Tanaka, Kazuhiro; Sato, Toshiyuki; Tsukamoto, Hiroshi; Suzuki, Katsuya
Cavitation phenomena in a pump unit as well as internal flows can be analysed by CFD codes with meaningful precision. However, it is difficult to analyse the dynamic characteristics of cavitating pump systems such as cavitation compliance and mass flow gain factor. The characteristic parameters on pump cavitation are studied through CFD calculations on cavity volume and the results are related the system bondgraphs in a lumped parameter system. The cavitation compliance can be represented by 1-port C element and mass flow gain factor can be represented not only by 1-port R element as flow resistance but also by 1-port I element as fluid inertia.